2015
DOI: 10.1155/2015/830809
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Food Safety Knowledge Base Applicable in Crisis Situations and Beyond

Abstract: In case of contamination in the food chain, fast action is required in order to reduce the numbers of affected people. In such situations, being able to predict the fate of agents in foods would help risk assessors and decision makers in assessing the potential effects of a specific contamination event and thus enable them to deduce the appropriate mitigation measures. One efficient strategy supporting this is using model based simulations. However, application in crisis situations requires ready-to-use and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The Konstanz Information Miner (KNIME) [7,15] framework was chosen as a programming environment to implement RASNEX, since it is centered on data mining and data science. KNIME allows users to graphically program by building so-called workflows that combine software modules with diverse purposes, called nodes, to process data [16]. Edges define the information flow between nodes.…”
Section: Programming Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The Konstanz Information Miner (KNIME) [7,15] framework was chosen as a programming environment to implement RASNEX, since it is centered on data mining and data science. KNIME allows users to graphically program by building so-called workflows that combine software modules with diverse purposes, called nodes, to process data [16]. Edges define the information flow between nodes.…”
Section: Programming Environmentmentioning
confidence: 99%
“…It is possible to import and combine many types of data into KNIME and to automatically create reports. In terms of risk management, the modular workflow-based approach [16] leads to a transparent, reproducible and transferable result. The KNIME platform includes different data analysis features allowing for applications in different research fields, e.g.…”
Section: Programming Environmentmentioning
confidence: 99%
“…Falenski et al [7] conducted an experiment to evaluate whether ready-to-use software-based models of food safety crises could help communicate risk quickly and efficiently to the public. The authors found that read-to-use models worked best in extreme cases of food safety compromise, like bioterrorism-type food contamination.…”
Section: Risk Communicationmentioning
confidence: 99%
“…In the case of the food chain, actions taken need to be swift and efficient. The situation is even more urgent and requires extra efforts when human health is at risk [7].…”
mentioning
confidence: 99%